2022
DOI: 10.3390/ma15030991
|View full text |Cite
|
Sign up to set email alerts
|

Promoters for Improved Adhesion Strength between Addition-Cured Liquid Silicone Rubber and Low-Melting-Point Thermoplastic Polyurethanes

Abstract: A polydimethylsiloxane armed with epoxy, alkoxy and acrylate groups was synthesized from silanol terminated-PDMS and epoxy and acrylate groups functionalized silane coupling agents, and utilized as the adhesion promoter (AP) to prepare addition-cured liquid silicone rubber that exhibited self-adhesion ability (SA-LSR) with biocompatible thermoplastic polyurethanes (TPU) sheets. The structural characteristics of AP were characterized by Fourier transform infrared (FTIR) spectroscopy, which demonstrated the stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The peak observed at 1261 cm −1 is attributed to the bending vibration of C-H in the methyl group bonded to the silicone atom, whereas the peaks at 2962 cm −1 and 2906 cm −1 are associated with the stretching vibration of C-H [22]. The absorption peaks observed at 1020 cm -1 and 1095 cm -1 are indicative of the Si-O-Si bond [22], while the absorption peak at 1413 cm -1 corresponds to the Si-C bond [23].The absorption peak at 1413 cm -1 corresponds to the characteristic of Si-C [23], while the stretching vibration peak at 2837 cm -1 is indicative of O-CH3 [24]. The presence of a weak hydroxyl characteristic absorption peak at 3400-3600 cm -1 [24] is hypothesized to be a result of the hydrolysis of the methoxy group during testing.…”
Section: The Impact Of Capping Agent Type On the Efficacy Of Cappingmentioning
confidence: 99%
“…The peak observed at 1261 cm −1 is attributed to the bending vibration of C-H in the methyl group bonded to the silicone atom, whereas the peaks at 2962 cm −1 and 2906 cm −1 are associated with the stretching vibration of C-H [22]. The absorption peaks observed at 1020 cm -1 and 1095 cm -1 are indicative of the Si-O-Si bond [22], while the absorption peak at 1413 cm -1 corresponds to the Si-C bond [23].The absorption peak at 1413 cm -1 corresponds to the characteristic of Si-C [23], while the stretching vibration peak at 2837 cm -1 is indicative of O-CH3 [24]. The presence of a weak hydroxyl characteristic absorption peak at 3400-3600 cm -1 [24] is hypothesized to be a result of the hydrolysis of the methoxy group during testing.…”
Section: The Impact Of Capping Agent Type On the Efficacy Of Cappingmentioning
confidence: 99%
“…For example, Kizilkan et al 9 treated the surface of silicone elastomer with air plasma, resulting in a 30% increase in adhesion. The second approach is to add adhesion promoters to the silicone elastomers precuring system, such as Wu et al 10 developed boron-modified polydimethylsiloxane (PDMS-B) and epoxy alkoxy bifunctionalized tetramethylcyclotetrasiloxane (D 4 HMSEP) as coadhesive promoters. The third approach is to modify polysiloxanes by introducing reactive functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned methods can effectively improve the adhesion of LSR to various substrates; however, both methods are time-consuming and complicated processes, and they are harmful to the environment. Therefore, the addition of adhesion promoters into LSR to provide a self-adhesive capacity has spurred intensive research interest due to the simple and scalable process and eco-friendly properties [ 29 , 30 , 31 , 32 , 33 ]. Pan et al reported a vinyl and epoxy groups-functionalized silane oligomer and used it as an adhesion promoter to prepare a self-adhesive addition-cure silicone encapsulant [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…These reactive groups (i.e., epoxy, alkoxy and methacryloxy groups)-containing adhesion promoters generally demonstrated their great improvement in bonding performance at high working temperatures (>120 °C). However, most of the adhesion promoters are unable to offer an efficient adhesion ability for LSR at moderate curing temperatures (e.g., 80 °C) [ 31 , 32 , 33 ]. Therefore, it remains a challenge to achieve efficient encapsulation and provide long-term reliable protection for temperature-sensitive electronic devices.…”
Section: Introductionmentioning
confidence: 99%